2016
DOI: 10.1177/0269881116647506
|View full text |Cite
|
Sign up to set email alerts
|

Lisdexamfetamine reduces the compulsive and perseverative behaviour of binge-eating rats in a novel food reward/punished responding conflict model

Abstract: Compulsive and perseverative behaviour in binge-eating, female, Wistar rats was investigated in a novel food reward/punished responding conflict model. Rats were trained to perform the conditioned avoidance response task. When proficient, the paradigm was altered to a food-associated conflict test by placing a chocolate-filled jar (empty jar for controls) in one compartment of the shuttle box. Entry into the compartment with the jar triggered the conditioning stimulus after a variable interval, and foot-shock … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 49 publications
2
39
0
Order By: Relevance
“…Oral lisdexamfetamine dimesylate (LDX), a prodrug of dextroamfetamine, is currently the only drug to be approved in the USA for the treatment of moderate to severe BED in adult patients [ 225 ]. When given acutely in a female rat BED model, LDX attenuated binge-eating of chocolate without influencing the consumption of normal chow or affecting the bodyweight of the animals [ 226 ] and reduced impulsiveness and perseverative behaviour of binge-eating rats in a novel food reward/punished responding conflict model [ 227 , 228 ]. Pharmacological characterisation indicated that LDX attenuates binge-eating in part by indirect activation of α1-adrenergic and possibly also dopamine D1 receptors in the CNS, but α2-adrenergic and D2 receptors are not involved [ 226 ].…”
Section: Binge Eating Disorder a “Full-fledged” Pathologymentioning
confidence: 99%
“…Oral lisdexamfetamine dimesylate (LDX), a prodrug of dextroamfetamine, is currently the only drug to be approved in the USA for the treatment of moderate to severe BED in adult patients [ 225 ]. When given acutely in a female rat BED model, LDX attenuated binge-eating of chocolate without influencing the consumption of normal chow or affecting the bodyweight of the animals [ 226 ] and reduced impulsiveness and perseverative behaviour of binge-eating rats in a novel food reward/punished responding conflict model [ 227 , 228 ]. Pharmacological characterisation indicated that LDX attenuates binge-eating in part by indirect activation of α1-adrenergic and possibly also dopamine D1 receptors in the CNS, but α2-adrenergic and D2 receptors are not involved [ 226 ].…”
Section: Binge Eating Disorder a “Full-fledged” Pathologymentioning
confidence: 99%
“…This “binge-like” feeding has been shown to result in more significant weight gain than was observed with continuous access to the same diet—as is used in models of diet-induced obesity ( 20 ). Prior work has also demonstrated that chronic, irregular, limited access to palatable food can result in compulsive feeding behavior ( 21 , 22 ) and increased impulsivity ( 23 ). Palatable sweet-fat and regular house chow consumption were measured during all limited access sessions.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we used an established rat model of binge eating to produce binge-like feeding behavior ( 18 20 ). Similar rodent models of binge eating have resulted in weight gain ( 20 ), compulsive feeding behavior ( 21 , 22 ) and increased impulsivity ( 23 ) thus displaying traits commonly observed in appetitive disorders like substance use and binge eating disorder. It is important to acknowledge, however, that this is a pre-clinical approximation of the clinical condition, and many successful pharmacologic trials using this rodent/rat model have failed to translate clinically with the exception of lisdexamfetamine ( 24 , 25 ).…”
Section: Introductionmentioning
confidence: 99%
“…This “binge-like” feeding has been shown to result in more significant weight gain than is observed with continuous access to the same diet -- as is used in models of diet-induced obesity [18]. Prior work has also demonstrated that chronic, irregular, limited access to palatable food can result in compulsive feeding behavior[21, 22] and increased impulsivity [23]. Palatable sweet-fat and regular house chow consumption was measured during all limited access sessions.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we used an established rat model of binge eating to produce binge-like feeding behavior [1820], Similar rodent models of binge eating have resulted in weight gain[18], compulsive feeding behavior[21, 22] and increased impulsivity[23] thus displaying problems in overlapping psychological domains to patients with binge eating disorder. It is important to acknowledge however, that this is merely a pre-clinical approximation of the clinical condition and many successful pharmacologic trials using this rodent/rat model have failed to translate clinically with the exception of lisdexamfetamine [24, 25].…”
Section: Introductionmentioning
confidence: 99%